Design Of An Operations Strategy-Based Framework To Align Demand And Capacity In A Crsytal Ice Manufacturing SME Within The Cold-Chain Industry - Maudy Farras Raihan; Dermawan Wibisono (LP2M IAIN Palopo, 2026)
This study examines the mismatch between production capacity, market demand, and distribution performance at a small and medium-sized enterprise (SME) producing ice crystals (Company A) in the cold chain industry. The company operates two machines with a total capacity of 10 tonnes per day, but actual sales volume only reaches 4-5 tonnes per day. This situation has resulted in low production utilisation, limited distribution coverage. Operational data for 2024-2025 shows that customer demand fluctuates on a daily, weekly, and hourly basis, while ordering behaviour is sudden, preventing the company from optimally planning production and distribution routes. The capacity of five motor couriers within a 12 km radius also becomes a bottleneck during peak hours, hindering delivery accuracy.Based on these conditions, this study formulates the problem of how to align production capacity, market demand, and distribution performance by determining the operational performance objectives; quality, speed, reliability, flexibility, and cost that need to be prioritised. The research design uses a mixed method case study with a quantitative dominance. Internal archive data analysis was conducted to calculate production utilisation, distribution utilisation, sales-to-output ratio, and demand-capacity gap stability. Next, six internal experts (the owner, administrative staff, two production operators, and two couriers) provided assessments through the Analytical Hierarchy Process (AHP), and the results were tested for consistency before being combined into group priority weights.The results of the study show that there is a consistent mismatch between installed capacity and actual demand. Average production utilisation is at 34-36%, while distribution loads accumulate during morning and afternoon peak hours. AHP analysis shows that cost, speed, and reliability are the top priorities for improving operational performance, in line with the patterns of inefficiency apparent in the operational data. This study in the discussion section highlights that distribution responsiveness, minimisation of inefficient costs of operations, and provision consistency in the fulfilment of services are essential in harmonising capacity and demand. The combination of operational results and AHP priorities provides the design of an alignment-based framework of an operational strategy. Suggestions on future research include creating a digital system that uses real-time data and increasing investigation into other cold chain SMEs in order to ensure that this strategic framework is more externally valid.